Measurement of high-Q2 neutral-current e+p deep inelastic scattering cross-sections at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Abbiendi, G; et al. (1999)
The e+p neutral-current deep inelastic scattering differential cross-sections dσ/dQ2, for Q2 > 400 GeV2, dσ/dx and dσ/dy, for Q2 > 400, 2500 and 10000 GeV2, have been measured with the ZEUS detector at HERA. The data sample of 47.7 pb-1 was collected at a center-of-mass energy of 300 GeV. The cross-section, dσ/dQ2, falls by six orders of magnitude between Q2 = 400 and 40000 GeV2. The predictions of the Standard Model are in very good agreement with the data. Complementing the observations of time-like Z° contributions to fermion-antifermion annihilation, the data provide direct evidence for the presence of Z° exchange in the space-like region explored by deep inelastic scattering.